Infiltração marginal de restauração temporária após o preparo de pino intrarradicular com ou sem impermeabilização - Cosme-Silva, Leopoldo; Viola, Naiana Viana; de Carvalho, Leon Franco; Khoury, Rayana Duarte [UNESP]; Gomes Filho, João Eduardo; de Carvalho, Elaine Manso Oliveira Franco (Editora Cubo, 2017)
Objective: This study evaluated the leakage volume of 1% Rhodamine B which received or not an internal waterproofing material. The hypothesis is that the waterproofing reduces microleakage. Material and Methods: Forty-two human teeth were selected for this study. After access, preparation, and filling of root canals, the teeth were divided into 3 groups: GI – sealed with Cimpat Blanc®, without intraradicular post/core preparation; GII - sealed with Cimpat Blanc®, with intraradicular post/core preparation, and GIII – sealed with Cimpat Blanc®, with intraradicular post/core preparation and internal waterproofing material with ethyl cyanoacrylate. T-test was used to analyze difference between initial and final weight and there was difference (p < 0.05). To analyze infiltration of the colorant, the volume was the comparison variable. Results: Shapiro Wilktest was applied and showed normal distribution of the variables. ANOVA (p = 0.0013/p<5%) applied and determined a statistical difference between the groups. When comparing the groups together, GIII show the smallest leakage rate when compared with the other groups, being statistically different (Tukey test - p < 0.5). Conclusion: In endodontically treated teeth receiving temporary restoration, the use of ethyl cyanoacrylate as internal waterproofing material is effective in preventing microleakage.
Marginal leakage of temporary restoration after intraradicular post preparation with or without waterproofing
Keywords: Coloring agents; Dental leakage; Dental restoration; Endodontics; Temporary